ANALYSIS OF VENDOR PAYMENT PROCEDURES BASED ON THE STANDARD OPERATING PROCEDURES (SOP) OF THE FINANCE DIVISION AT PT PKM, JAKARTA, INDONESIA (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine the implementation of the Vendor Payment Procedure based on the Standard Operating Procedures (SOP) of the Finance Division at PT PKM, North Jakarta. Specifically, the study investigates the existing vendor payment procedures, identifies the challenges encountered during their implementation, and explores the solutions adopted to address these issues. Data were collected using a qualitative approach through direct observation of the vendor payment process The findings reveal several challenges in the implementation of the vendor payment procedure, including delays and incomplete submission of payment documents, the unavailability of Sub-Branch Office (Kantor Cabang Pembantu/KCP) information for newly registered vendors' banks, which complicates bank transfer transactions, and the continued use of a manual document filing system. To overcome these challenges, the company conducts regular training programs for employees at both the head office and operational units to improve their understanding of their respective job responsibilities and ensure compliance with the established SOP for vendor payment processing. These initiatives are expected to enhance the efficiency, accuracy, and effectiveness of the vendor payment process within the Finance Division.